2022
DOI: 10.1177/20420188221099346
|View full text |Cite
|
Sign up to set email alerts
|

Bone health in transgender people: a narrative review

Abstract: Bone health in transmen and transwomen is an important issue that needs to be evaluated by clinicians. Prior to gender-affirming hormone treatment (GAHT), transwomen have lower bone mineral density (BMD) and a higher prevalence of osteopenia than cismen probably related to external factors, such as hypovitaminosis D and less physical activities. Gonadotropin-releasing hormone (GnRH) analogues in transgender youth may cause bone loss; however, the addition of GAHT restores or at least improves BMD in both trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…This is consistent with previous studies showing that TW, even before the start of any hormonal intervention, already have lower bone mass, a higher frequency of osteoporosis, and smaller bone size than cis men. [9][10][11]18,25 However, it has also been reported that the average BMD in the hip and spine of TW does not differ from that of cis men. 15 Taken together, these results suggest that spine and hip BMD can often be low in TW, which is concerning for its potential consequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous studies showing that TW, even before the start of any hormonal intervention, already have lower bone mass, a higher frequency of osteoporosis, and smaller bone size than cis men. [9][10][11]18,25 However, it has also been reported that the average BMD in the hip and spine of TW does not differ from that of cis men. 15 Taken together, these results suggest that spine and hip BMD can often be low in TW, which is concerning for its potential consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In studies and reviews it has been reported that TW tend to have a lower BMD than cis men (whose biological sex is congruent with gender identity and expression), even before starting GAHT. [7][8][9][10][11] It has been suggested that the lower BMD in TW may be because they do less physical activity, have less muscular development, and have a higher risk of hypovitaminosis D. 7,8,10,12 In Belgium, 26% of TW presented a BMD below the expected range for their age in the spine and 2% in the hip. 13 Likewise, among TW, the density of trabecular bone was positively associated with the use of GAHT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone density in transmasculine adults appears to be similar to the general population at baseline and after taking GAHT. 64 , 65 Although testosterone initiation often leads to cessation of menses and thus a relative deficiency in estradiol, several studies, including a meta-analysis by Singh-Ospina et al , 66 have shown stable bone mineral density (BMD) in transmasculine adults on GAHT. Testosterone use by transmasculine adults alters body composition by increasing muscle mass, decreasing fat mass and also likely has direct action on the bone.…”
Section: Masculinizing Gahtmentioning
confidence: 99%
“…Our critical appraisal concludes these studies do not support the notion of an unacceptable risk to bone health in TGD youth, which aligns with endocrine society guidelines and others conducting high-quality reviews. 4,8 This leads to an important question: how can pharmacists mitigate any risk of negative bone health outcomes? TGD persons experience food insecurity and poor nutritional knowledge, which may lead to poor dietary intake of calcium and vitamin D. 9 Pharmacists are well-equipped to counsel patients on dietary intake, screening for deficiencies, and recommending appropriate supplementation.…”
mentioning
confidence: 99%